The effect of applying mechanisms to stimulate working memory on the learner achievement in the field of art education - Sakini, Suhad Jawad (International Journal of Psychosocial Rehabilitation, 2020)
The obstacles that the learner encounters during the acquisition of educational experience constitute a starting point for building the current research goal that aims to test the effect of the application of working memory mechanisms in the achievement of students of the Department of Art Education at the Faculty of Basic Education at Al-Mustansiriya University of art education materials through experimenting with the automatic formation and the interaction of elements compared to the usual way in Technical education lessons, so it required that random selection of two experimental groups and one control group, comprising (30) students for each group, so that the mechanism of automatic formation is applied to the first experimental group and the mechanism of interaction of elements is applied to the second experimental group and compare each group with the usual way that is applied to The control group and then the results are monitored in the light of the statistical indicators that result from conducting the cognitive achievement test that was designed in the current research. The results showed that there were statistically significant differences at the level (0.05) in favor of experimental groups compared to the usual method in the post-application of this test that Demonstrate an effective effect of the automatic formation mechanisms and the interaction of elements compared to The usual method and in various formats stimulated the working memory of the learner towards the acquisition of art education materials.